2016
DOI: 10.1111/evj.12639
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical ultrasonographic abnormalities of the suspensory ligament branches in National Hunt racehorses

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…In the current series, forelimbs were more commonly affected than hindlimbs which is in accord with previous reports of SLB injuries in racing Thoroughbreds [1,2,12]. Sidedness (left fore most common) was evident in a study of SLB lesions in Thoroughbred yearlings in the USA [1]; this may be a reflection of anticlockwise training direction as it has not been recognised in the current group or other studies of racing Thoroughbreds from the UK [2,3]. Studies of Thoroughbred racehorses have consistently identified abnormalities in medial more frequently than lateral SLB [2,3,16].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the current series, forelimbs were more commonly affected than hindlimbs which is in accord with previous reports of SLB injuries in racing Thoroughbreds [1,2,12]. Sidedness (left fore most common) was evident in a study of SLB lesions in Thoroughbred yearlings in the USA [1]; this may be a reflection of anticlockwise training direction as it has not been recognised in the current group or other studies of racing Thoroughbreds from the UK [2,3]. Studies of Thoroughbred racehorses have consistently identified abnormalities in medial more frequently than lateral SLB [2,3,16].…”
Section: Discussionsupporting
confidence: 90%
“…Sidedness (left fore most common) was evident in a study of SLB lesions in Thoroughbred yearlings in the USA [1]; this may be a reflection of anticlockwise training direction as it has not been recognised in the current group or other studies of racing Thoroughbreds from the UK [2,3]. Studies of Thoroughbred racehorses have consistently identified abnormalities in medial more frequently than lateral SLB [2,3,16]. Lesions reported in the current study were more common laterally than medially but none of the previous publications made any differentiation of lesion type or location within the SLB.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This cross‐sectional study by A. Fairburn and colleagues in the UK aimed to investigate the prevalence of subclinical ultrasonographic abnormalities of the suspensory ligament branches (SLBs). It also aimed to establish cross‐sectional areas of SLBs in the National Hunt population .…”
Section: Suspensory Injuries In National Hunt Racehorsesmentioning
confidence: 99%